Pengaruh Metode Inkuiri Terhadap Keaktifan Belajar Dan Keterampilan Menyimpulkan Pada Mata Pelajaran Biologi Kelas X MAN 1 Kabupaten Lombok Barat - Risa Umami; Bunga Adeliana Lestari; Nurfadila Arifin; Aulia Zulfaeda (Otus Education: Jurnal Biologi dan Pendidikan Biologi, 2023)
This research aims to determine the effect of the inquiry method on active learning and concluding skills in the biology subject class X MAN 1 of West Lombok on ecosystem material. This research uses a quantitative approach with a quasi experimental type of research. The population in this study were students of X MAN 1 West Lombok. Sampling was taken using a saturated sampling technique. The samples for this research were students in classes X MIPA 1 and X MIPA 2. The research design used a nonequivalent control group design. This research instrument is in the form of observations and test questions. Research data analysis used statistical tests, namely the t-test using SPSS 22. The research results showed that there was an influence of the inquiry method on learning activeness (P<0.05) and concluding skills (P<0.05). So, this method is effectively implemented in learning to maximize mastery of the material that has been covered by the teacher.